OS EFEITOS JURÍDICOS DA APRESENTAÇÃO E PAGAMENTO DO CHEQUE PÓS-DATADO ANTES DA DATA PACTUADA - Carmo, Juliana S. d.; Santos, Ariana B. d.; Sulzbach, Camila C.; Feversani, Francini (Salão do Conhecimento, 2013)
Resumo